Color Deficiency Activity Book sebagai Deteksi Dini Buta Warna pada Anak TK - Tatha Putri Kinanthi; Evelyne Henny Lukitasari; Ahmad Khoirul Anwar (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2026)
Color blindness (CVD) is a condition in which the eye cannot distinguish certain color wavelengths or cannot distinguish colors at all. This condition can be detected with several tests, including the Ishihara Method or the Farnsworth Munsell Method. Both of these tests are not suitable for kindergarten children because the numbers used in the Ishihara Method do not match the child's cognitive level, and the repetitive color chip ordering method in the Farnsworth Munsell Method tends to make children bored. This contradicts expert opinion that recommends eye health tests be carried out as early as possible, or at the age of 3-5 years. Therefore, there is an urgent need for early-detection media for color blindness in kindergarten children that are appropriate to the child's cognitive level and interests. This research aims to design a prototype activity book as a medium for early detection of color blindness in kindergarten children, focusing on adapting the color hues of the Farnsworth Munsell color blindness test method into several interactive activities and reducing the use of large nominal numbers in the Ishihara test method. This design uses Design Thinking methods, reaching the prototype stage, to produce an initial visualization of an interactive activity book for early detection of color blindness in kindergarten children.